2017
DOI: 10.1103/physrevb.96.195126
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Bloch excitations in Mott matter

Abstract: We develop a unified theoretical picture for excitations in Mott systems, portraying both the heavy quasiparticle excitations and the Hubbard bands as features of an emergent Fermi liquid state formed in an extended Hilbert space, which is non-perturbatively connected to the physical system. This observation sheds light on the fact that even the incoherent excitations in strongly correlated matter often display a well defined Bloch character, with pronounced momentum dispersion. Furthermore, it indicates that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…(15) with respect to ψ(Γ, γ) we find the results shown in figure 3. In agreement with [48], the g-GW with N = 3 displays for U ∈ [U c1 , U c2 ] the metal-insulator coexistence found in DMFT. The values of the spinodal points, U c1 /2t 1.85 and U c2 /2t 2.88, are slightly underestimated with respect to DMFT, U c1 /2t 2.39 and U c2 /2t 2.94 [58][59][60][61].…”
Section: B Paramagnetic Mott Transition At H =supporting
confidence: 73%
See 1 more Smart Citation
“…(15) with respect to ψ(Γ, γ) we find the results shown in figure 3. In agreement with [48], the g-GW with N = 3 displays for U ∈ [U c1 , U c2 ] the metal-insulator coexistence found in DMFT. The values of the spinodal points, U c1 /2t 1.85 and U c2 /2t 2.88, are slightly underestimated with respect to DMFT, U c1 /2t 2.39 and U c2 /2t 2.94 [58][59][60][61].…”
Section: B Paramagnetic Mott Transition At H =supporting
confidence: 73%
“…The main difficulty in this context is finding a variational wavefunction that can faithfully describe a Mott insulator. We shall use here a recent extension [48] of the Gutzwiller wavefunction, which has been named ghost Gutzwiller wavefunction (g-GW) and reads…”
Section: A the Variational Ghost-gutzwiller Wavefunctionmentioning
confidence: 99%
“…Yet from our calculation, we note that the change in the double occupancy and the renormalization factor z is rather smooth, hence the metal to insulator transition appears to be a crossover based on our CMR calculation. It has been shown that the Mott physics such as the inter-site spin correlations and incoherent double excitations may not be well described by Gutzwiller approximation (GA) [37][38][39]. The lack of sharp Mott transition in 1D hydrogen chain shown in Fig.…”
Section: Fig 2 Double Occupancy Weight D and The One Electron Renormmentioning
confidence: 99%
“…There have been efforts to access Hubbard models using the GWF [21][22][23][24][25][26]. On one hand, the GA has been widely applied although it sometimes fails to give an accurate description of the model system [21].…”
Section: Introductionmentioning
confidence: 99%